A Novel Approach to Reducing Workers Compensation Costs in a Multicenter Hospital System. Issue 1 (January 2018) - Ullucci, Paul A.; Scott, Joseph; Silverman, Bradley
Abstract : Objective: To evaluate the efficacy of an injury prevention and monitoring program implemented by athletic trainers to reduce workers compensation costs in a hospital system with multiple centers and locations. Methods: A retrospective analysis of workers compensation claims (ie, lost days, light days, and incurred costs) was performed to compare injury data from 2 years before to 2 years after the start of the program. Results: The program significantly reduced the organization's incurred costs by 46.7% ( P = 0.031) and light days by 44% ( P = 0.022). Lost days were found to decrease by 37%, however, this decrease was not statistically significant ( P = 0.078). Conclusions: Athletic trainers, using their knowledge of anatomy, biomechanics, ergonomics, injury management, and rehabilitation, can effectively prevent and reduce workers compensation costs in a multicenter hospital system.